Cash or Card? An Explorative Analysis of Consumers’ Payment Behaviour in Hungary - Végső, Tamás; Belházyné Illés, Ágnes; Bódi-Schubert, Anikó (Public Finance Quarterly, 2023)
The main purpose of this study is to explore the payment patterns and cash usage behaviour of the Hungarian public and examine the effects of age, income, education and other socio-demographic factors on these habits. In this regard, we focus especially on the public’s general attitude towards cash and their subjective payment preferences. Our research is primarily based on data acquired from a questionnaire-based survey of 1,500 people, and we compare the lessons learned from it with international examples. We find that the Hungarian population is clearly pro-cash, and this is especially true for those with lower income and lower educational attainment, the economically inactive and the youngest and eldest age groups. A significant proportion uses cash only out of necessity due to the deficiencies of the payment infrastructure, but they are outnumbered by those who would not want to give up banknotes and coins in the future, for a variety of, typically, subjective reasons. The reasons include, for example, the quickness of cash payment and better control over spending, but habits also play a significant role in payment choices.